Intrinsic functional network organization in high-functioning adolescents with autism spectrum disorder - Redcay, Elizabeth; Moran, Joseph M.; Mavros, Penelope L.; Tager-Flusberg, Helen; Gabrieli, John D.; Whitfield-Gabrieli, Susan (Frontiers in Human Neuroscience, 2013)
Converging theories and data suggest that atypical patterns of functional and structural connectivity are a hallmark neurobiological feature of autism. However, empirical studies of functional connectivity, or, the correlation of MRI signal between brain regions, have largely been conducted during task performance and/or focused on group differences within one network (e.g., the default mode network). This narrow focus on task-based connectivity and single network analyses precludes investigation of whole-brain intrinsic network organization in autism. To assess whole-brain network properties in adolescents with autism, we collected resting-state functional connectivity MRI (rs-fcmri) data from neurotypical adolescents (NT) and adolescents with autism spectrum disorder (ASD). We used graph theory metrics on rs-fcmri data with 34 regions of interest (i.e., nodes) that encompass 4 different functionally-defined networks: cingulo-opercular, cerebellar, fronto-parietal, and default mode (DMN) (Fair et al., 2009). Contrary to our hypotheses, network analyses revealed minimal differences between groups with one exception. Betweenness centrality, which indicates the degree to which a seed (or node) functions as a hub within and between networks was greater for participants with autism for the right lateral parietal region of the DMN. Follow-up seed-based analyses demonstrated greater functional connectivity in ASD than NT groups between the right lateral parietal seed and another region of the DMN, the anterior medial prefrontal cortex. Greater connectivity between these regions was related to lower ADOS scores (i.e. lower impairment) in autism. These findings do not support current theories of underconnectivity in autism, but, rather, underscore the need for future studies to systematically examine factors that can influence patterns of intrinsic connectivity such as autism severity, age, and head motion.